Protocol incorporating airway CT decreases negative bronchoscopy rates for suspected foreign bodies in pediatric patients. (June 2018) - Ahmed, Omar G.; Guillerman, Robert P.; Giannoni, Carla M.
Abstract: Background: Foreign body aspiration (FBA) is the 4th leading cause of death in children between the ages 1-5. Although direct laryngoscopy and bronchoscopy (DL&B) is the reference standard for diagnosis of pediatric airway foreign bodies, there is a high negative bronchoscopy rate, exposing patients to unnecessary operative and anesthetic risks and costs. Methods: A clinical care protocol entailing the selective use of low-dose non-contrast airway computed tomography (CT) for children with an intermediate risk for FBA on the basis of clinical exam and chest radiography was implemented to decrease the negative DL&B rate. A retrospective review was conducted to compare negative bronchoscopy rates before and after implementation of the new protocol and the diagnostic performance characteristics of airway CT for airway foreign bodies were analyzed. Results: After implementation of the airway FB clinical care protocol entailing selective airway CT, the overall negative bronchoscopy rate decreased from an institutional historical rate of 37% (54/145) to 17% (10/56) (p = .06). The overall sensitivity, specificity, and positive and negative predictive value of airway CT for FB was 91%, 100%, 100%, and 97% respectively. Conclusions: Low-dose non-contrast airway CT is highly sensitive and specific for airway foreign bodies, and its selective use in a clinical care protocol for children with suspected foreign body aspiration could greatly reduce the negative bronchoscopy rate, thereby decreasing operative risks and costs.